Percutaneous Cordotomy for Pain Palliation in Advanced Cancer: A Randomized Clinical Trial Study Protocol. Issue 2 (3rd February 2020) - Viswanathan, Ashwin; Vedantam, Aditya; Williams, Loretta A; Koyyalagunta, Dhanalakshmi; Abdi, Salahadin; Dougherty, Patrick M; Mendoza, Tito; Bassett, Roland L; Hou, Ping; Bruera, Eduardo
Abstract: BACKGROUND: Cancer pain, one of the most common symptoms for patients with advanced cancer, is often refractory to maximal medical therapy. A controlled clinical trial is needed to provide definitive evidence to support the use of ablative procedures such as cordotomy for patients with medically refractory cancer pain. OBJECTIVE: To assess the efficacy of cordotomy for patients with unilateral advanced cancer pain using a controlled clinical trial study design. The secondary objectives are to define the patient experience of cordotomy for medically refractory cancer pain as well as to determine the utility of magnetic resonance imaging as a non-invasive biomarker for successful cordotomy. METHODS: We will undertake a single-institution, double-blind, sham-controlled clinical trial of cordotomy in patients with refractory cancer pain. Patients in the cordotomy arm will undergo a percutaneous computed tomography-guided cordotomy at C1-C2, while patients in the control arm will undergo a similar procedure where the needle will not penetrate the thecal sac. The primary endpoint will be the reduction in pain intensity, as measured by the Edmonton Symptoms Assessment Scale. EXPECTED OUTCOMES: We expect that patients randomized to cordotomy will have a significantly greater reduction in pain intensity than those patients randomized to the control surgical intervention. DISCUSSION: This randomized clinical trial comparing cordotomy with a control intervention will provide the level of evidence necessary to determine whether cordotomy should be the standard of care intervention for patients with advanced cancer pain.